A LOOK AT THE LYRICS OF ERKIN VOHIDOV - Sarvinoz JAMOLOVA (Western European Studies, 2024)
In this article, The Hero of Uzbekistan, people's poet Erkin Vohidov studied the specific spiritual and spiritual world of the lyrical hero
Keywords: psyche; poem; word miracle